Analyzing study for the 3D potential Yu-Toda-Sasa-Fukuyama equation in the two-layer liquid medium - Ismael, Hajar F.; Okumus, Israfil; Aktuerk, Tolga; Bulut, Hasan; Osman, M. S. (Elsevier, 2024)
In this work, we use the (m + 1 /G' )-expansion method and the Adomian decomposition method to study the 3D potential Yu-Toda-Sasa-Fukuyama (3D-pYTSF) equation which has a good application in the twolayer liquid medium. For the first time, the (m + 1 /G' )-expansion and the Adomian decomposition methods are used to establish novel exact wave solutions and to study some numerical solutions for the 3DpYTSF equation, respectively. Through using the analytical method, kink-type wave, singular solution and some complex solutions to the suggested equation are successfully revealed. The obtained wave solutions are represented with some figures in 3D and contour plots. (c) 2022 Shanghai Jiaotong University. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license ( http://creativecommons.org/licenses/by-nc-nd/4.0/ )
Keywords: ( m+1 /G ')-expansion method; Complex solutions; Adomian decomposition method